2017
DOI: 10.1038/s41598-017-06886-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro significance of SOCS-3 and SOCS-4 and potential mechanistic links to wound healing

Abstract: Wound healing and the management of chronic wounds represent a significant burden on the NHS. Members of the suppressor of cytokine signalling (SOCS) family have been implicated in the regulation of a range of cellular processes. The current study aims to explore the importance of SOCS-3 and SOCS-4 in regulating cellular traits associated with wound healing. SOCS-3 over-expression and SOCS-4 knockdown mutant lines were generated and verified using q-PCR and western blotting in human keratinocytes (HaCaT) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Protein was extracted from PC‐3 EPLIN EXP and PC‐3 pEF6 cells and quantified by fluorometric protein quantification, as reported previously, and subsequently sent to Kinexus™ Bioinformatics (Kinexus Bioinformatics, Vancouver, British Columbia, Canada). Data were analyzed using several parameters including Globally Normalized Signal Intensity, z ratio and % change from control (CFC).…”
Section: Methodsmentioning
confidence: 99%
“…Protein was extracted from PC‐3 EPLIN EXP and PC‐3 pEF6 cells and quantified by fluorometric protein quantification, as reported previously, and subsequently sent to Kinexus™ Bioinformatics (Kinexus Bioinformatics, Vancouver, British Columbia, Canada). Data were analyzed using several parameters including Globally Normalized Signal Intensity, z ratio and % change from control (CFC).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the regulation of SOCS expression and its effects on wound healing. SOCS-1 and SOCS-5 modulate IL-4 signaling to regulate re-epithelialization and the tissue remodeling phase of wound healing [26,30,31], while SOCS-3 plays a role in regulating the inflammatory phase [40]. As SOCS-1, -3, and -5 are important factors involved in different phases of wound healing, the co-transfection of these genes is expected to improve the wound-healing function of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…SOC-1, -3, and -5 play important roles in the wound-healing process. Claire et al demonstrated that SOCS-1 plays a significant role in inflammatory inhibition [30], and Feng et al showed that overexpression of SOCS-3 is crucial for wound healing [21,31]. SOCS-5 also acts as a negative regulator of inflammatory cytokines [19].…”
Section: Introductionmentioning
confidence: 99%
“…13 HECV cells, available from several cellular banks, were used since they share the same origin of HUVECs and are considered a bloodstream model. [14][15][16][17][18][19] No antibiotic or antifungal solutions were added to standard or experimental medium to avoid any potential interference of these drugs with the cell culture. [20][21][22][23][24][25] All cell cultures were found to be mycoplasma-free on regular checks with Reagent Mycoplasma Set (Euroclone).…”
Section: Methodsmentioning
confidence: 99%